Effects of Home-Delivered Cognitive Behavioral Therapy (CBT) for Depression on Anxiety Symptoms among Rural, Ethnically Diverse Older Adults. Issue 3 (27th May 2017) - DiNapoli, Elizabeth A.; Pierpaoli, Christina M.; Shah, Avani; Yang, Xin; Scogin, Forrest
ABSTRACT: Background: We examined the effects of home-delivered cognitive-behavioral therapy (CBT) for depression on anxiety symptoms in an ethnically diverse, low resource, and medically frail sample of rural, older adults. Method: This was a secondary analysis of a randomized clincial trial with 134 rural-dwelling adults 65 years and older with decreased quality of life and elevated psychological symptomatology. Anxiety symptoms were assessed with the anxiety and phobic anxiety subscales of the Symptom Checklist-90-Revised (SCL-90-R). Results: Compared to a minimal support control condition, CBT for depression resulted in significantly greater improvements in symptoms of anxiety and phobic anxiety from pre-treatment to post-treatment. Conclusion: Home-delivered CBT for depression can be an effective treatment for anxiety in a hard-to-reach older populations. Clinical Implications: Additional research should explore integrated anxiety and depression protocols and other treatment modalities, including bibliotherapy or telehealth models of CBT, to reduce costs associated with its in home delivery. Flexibility in administration and adaptations to the CBT protocol may be necessary for use with vulnerable, rural older adults.